Influence of Brand Image, Product Quality, and Price on Digital TV Buying Interest in Indonesia: Pengaruh Citra Merek, Kualitas Produk, dan Harga terhadap Minat Beli TV Digital di Indonesia - Dwi Ayu Miftakhul Qiftiyah; Sumartik (Academia Open, 2024)
This study examines the impact of Brand Image, Product Quality, and Price on consumer buying interest in digital TV products in Mojokerto. Using a quantitative descriptive approach, data were collected from 100 respondents through online questionnaires and analyzed using multiple linear regression with SPSS. The results show that Brand Image, Product Quality, and Price significantly influence consumer interest. A positive Brand Image builds trust and preference, high Product Quality enhances perceived value, and competitive pricing motivates purchases. These findings suggest that companies should focus on these factors to boost consumer interest in digital TVs. Future research should investigate additional factors and expand to larger urban areas for broader insights. Highlight: Significant Impact: Key factors influence consumer interest in digital TVs. Positive Perception: Strong Brand Image builds consumer trust and preference. Value Perception: High Quality and competitive pricing boost product value. Keywoard: Brand Image, Product Quality, Price, Consumer Buying Interest, Digital TV